2013
DOI: 10.4236/jct.2013.48159
|View full text |Cite
|
Sign up to set email alerts
|

Cks1: Structure, Emerging Roles and Implications in Multiple Cancers

Abstract: Deregulation of the cell cycle results in loss of normal control mechanisms that prevent aberrant cell proliferation and cancer progression. Regulation of the cell cycle is a highly complex process with many layers of control. One of these mechanisms involves timely degradation of CDK inhibitors (CKIs) like p27Kip1 by the ubiquitin proteasomal system (UPS). Cks1 is a 9 kDa protein which is frequently overexpressed in different tumor subtypes, and has pleiotropic roles in cell cycle progression, many of which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 165 publications
(254 reference statements)
1
20
0
Order By: Relevance
“…P27 Kip1 is degraded in the late G1 phase via the ubiquitin–proteasome pathway [17]. The Cks1 protein is a member of the highly conserved family of Cks/Suc1 proteins which interact with Cdks and participates in numerous cellular processes including cell proliferation, growth and survival [18, 19]. One of well established mechanisms of Cks1 modulating cell cycle is to bind with the C-terminal of Skp2 to degrade p27 Kip1 and to promote cell cycle progression from G1 to S phase [7, 8, 18].…”
Section: Discussionmentioning
confidence: 99%
“…P27 Kip1 is degraded in the late G1 phase via the ubiquitin–proteasome pathway [17]. The Cks1 protein is a member of the highly conserved family of Cks/Suc1 proteins which interact with Cdks and participates in numerous cellular processes including cell proliferation, growth and survival [18, 19]. One of well established mechanisms of Cks1 modulating cell cycle is to bind with the C-terminal of Skp2 to degrade p27 Kip1 and to promote cell cycle progression from G1 to S phase [7, 8, 18].…”
Section: Discussionmentioning
confidence: 99%
“…This may further support the idea that cAMP/PKA signalling pathway might operate upstream of cell cycle control points (Saunders et al ., ). In addition, the roles of Cks1 in growth factor signalling pathways, including MAPK regulation, had been reported (Khattar and Thottassery, ). In this study, however, no physical interactions were detected between Cks1 and several components involved in MAPK signalling pathways and cell cycle control processes in Y2H assays, such as Pmk1 (MGG_09565), Mps1 (MGG_04943), Mst7 (MGG_00800), Cdc10 (MGG_06726), Cdc11 (MGG_03087) and Cdc12 (MGG_07466) (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in a variety of organisms have demonstrated that Cks1/Suc1 is required for modulating cell cycle control, maintaining cellular growth and transcriptional regulation (Hayles et al, 1986b;Hindley et al, 1987;Richardson et al, 1990;Tang and Reed, 1993;Patra and Dunphy, 1996;Khattar and Thottassery, 2013). In S. cerevisiae, disruption of CKS1 leads to cells defective in G 1 /S and G 2 /M phase transitions, as well as the ability to bud (Tang and Reed, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Cks1 is an evolutionarily conserved 9 kDa protein first identified as a component of yeast cyclin-Cdk complexes, which has been implicated in cell cycle progression, transcriptional regulation, and growth-signaling pathways [1]. Importantly, in the past few years, several studies, including ours, have demonstrated that Cks1 is highly upregulated in tumors [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 98%
“…Given its pleiotropic roles in the expression of tumorigenic phenotypes, inhibition of Cks1 has been suggested as a potential anticancer strategy [1]. Importantly, the therapeutic promise of such an approach has been validated in a myc-induced transgenic lymphoma model [13].…”
Section: Introductionmentioning
confidence: 99%